Cultures of Solidarity : Consciousness, Action, and Contemporary American Workers - Fantasia, Rick (Book collections on Project MUSE., 1989)
A commonplace assumption about American workers is that they lack class consciousness. This perception has baffled social scientists, demoralized activists, and generated a significant literature on American exceptionalism. In this provocative book, a you.